RETRACTED: Social ecology of interpersonal relationships among pensioners participating in the “Moscow Longevity” project - Litvinova Anna; Kotenev Igor; Kokurin Alexey; Kuznetsova Anna (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001